'Doing' Persuading: Actively Constructing Knowledge, Voice and Self. Issue 3 (3rd July 2018) - Davies, Molly
ABSTRACT: I explore a series of incidents in my English classroom, which occurred while I was preparing my students for their high-stakes GCSE English Language exam ('Paper 2: Writers' viewpoints and perspectives'). I thereby attempt to confront some of my own failings and biases with regard to non-fiction and the teaching of persuasive writing in particular, as well as to unleash the huge potential I now believe it offers, when combined with the multi-voiced space of a classroom, for creative play and the productive skills of English. In doing so I argue, drawing on Vygotskian notions of the internalisation of concepts and the developmental benefits of play, that in order for truly 'productive' learning to occur, students need agency and a sense of empowerment to construct knowledge together, and to experiment with and develop their understanding of and flexibility with their own 'voice'.